Contributing factors towards difficulties in generating ideas among technical students - Yee Mei Heong, Md Yunos Jailani, Hassan Razali, Mohamad Mimi Mohaffyza, Othman Widad, Tee Tze Kiong, (N/A, 2013)
Contributing factors towards difficulties in generating ideas among technical students by Yee Mei Heong, Md Yunos Jailani, Hassan Razali, Mohamad Mimi Mohaffyza, Othman Widad, Tee Tze Kiong,